Grï¿½neisen parameter for gases and superfluid helium - De Souza, Mariano [UNESP]; Menegasso, Paulo [UNESP]; Paupitz, Ricardo [UNESP]; Seridonio, Antonio [UNESP]; Lagos, Roberto E. [UNESP] (IOP Publishing, 2016)
The Grï¿½neisen ratio (Γ), i.e. the ratio of the thermal expansivity to the specific heat at constant pressure, quantifies the degree of anharmonicity of the potential governing the physical properties of a system. While Γ has been intensively explored in solid state physics, very little is known about its behavior for gases. This is most likely due to the difficulties posed in carrying out both thermal expansion and specific heat measurements in gases with high accuracy as a function of pressure and temperature. Furthermore, to the best of our knowledge a comprehensive discussion about the peculiarities of the Grï¿½neisen ratio is still lacking in the literature. Here we report on a detailed and comprehensive overview of the Grï¿½neisen ratio. Particular emphasis is placed on the analysis of Γ for gases. The main findings of this work are: (i) for the van der Waals gas Γ depends only on the co-volume b due to interaction effects, it is smaller than that for the ideal gas (Γ = 2/3) and diverges upon approaching the critical volume; (ii) for the Bose-Einstein condensation of an ideal boson gas, assuming the transition as first-order, Γ diverges upon approaching a critical volume, similarly to the van der Waals gas; (iii) for 4He at the superfluid transition Γ shows a singular behavior. Our results reveal that Γ can be used as an appropriate experimental tool to explore pressure-induced critical points.
Keywords: Grï¿½neisen parameter; phase transitions; specific heat; thermal expansion